2010
DOI: 10.1093/rpd/ncq168
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of electromagnetic fields from trams, trains and hybrid cars

Abstract: Electricity is used substantially and sources of electric and magnetic fields are, unavoidably, everywhere. The transportation system is a source of these fields, to which a large proportion of the population is exposed. Hence, investigation of the effects of long-term exposure of the general public to low-frequency electromagnetic fields caused by the transportation system is critically important. In this study, measurements of electric and magnetic fields emitted from Australian trams, trains and hybrid cars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 15 publications
2
39
0
Order By: Relevance
“…In a more recent paper [8], it is reported that magnetic fields measured in a hybrid car are much lower than the ICNIRP 1998 field reference levels, but no results taking into account additive effects were presented. Maximum fields of ∼15 μT (in the band 0.01-5 kHz) were recorded in a hybrid bus at the seat located closest to power cables during acceleration, deceleration, and driving at 25 km/h [9], but no information regarding the time variation of the magnetic field is provided.…”
mentioning
confidence: 99%
“…In a more recent paper [8], it is reported that magnetic fields measured in a hybrid car are much lower than the ICNIRP 1998 field reference levels, but no results taking into account additive effects were presented. Maximum fields of ∼15 μT (in the band 0.01-5 kHz) were recorded in a hybrid bus at the seat located closest to power cables during acceleration, deceleration, and driving at 25 km/h [9], but no information regarding the time variation of the magnetic field is provided.…”
mentioning
confidence: 99%
“…At present there already exist numerous norms which classify magnetic fields and the permitted exposure levels for humans. That is why in the face of development of hybrid and electric vehicles (Choromanski and Kowara, 2010) there emerges a potential threat to humans which has to be controlled (Halgamuge et al, 2010). Apart from the above described possibilities, use of a magnetometer offers an opportunity of direct measurement of the magnetic field generated by vehicles.…”
Section: Discussionmentioning
confidence: 99%
“…In urban rail transit system, propulsion motors are electrical, of alternating current (AC) or direct current (DC) types. Accordingly, the power supply could also be AC or DC (4). Such systems generate static magnetic field (SMF) and extremely low frequency magnetic fields (ELF-MF).…”
Section: Introductionmentioning
confidence: 99%
“…The average of minimum and maximum MF was measured at various locations inside the vehicles. According to their results, minimum ELF-MF values were 0.6, 0.01, 1.5, 0.5, and 0.3 mG measured at rear floor, middle floor, front floor, driver side seat, and above the train drivers' cabin, respec- (4).…”
Section: Introductionmentioning
confidence: 99%